Impact of Audit Committee Characteristics on Financial Performance Of companies Listed under Materials Sector in CSE - Kasthury, S.; Anandasayanan, S. (University of Kelaniya, 2020)
Audit committee functions as an indispensable mechanism by effectively communicating between internal and external auditors. This study aims to evaluate how the audit committee affects the entities, financial performance using a sample of companies from the material industry, out of 20 GICS industries listed in CSE. Only 14 companies were chosen out of the 23 companies in the material sector using the random sampling method. This study was based on secondary data where the data was obtained for these 14 companies from annual reports for the period from 2012 to 2019. The statistical techniques of descriptive statistics and regression analysis were utilized for analyzing the data. Earnings per share as a dependent variable and audit committee size, audit committee independence, audit committee financial expertise, audit committee meetings were considered as independent variables, furthermore firm size as control variables were utilized for undertaking the study. The findings revealed that the audit committee meetings has a significantly positive impact on earnings per share, whereas all the audit committee attributes excluding audit committee independence showed a positive influence over earnings per share.
Keywords: Audit Committee Financial Expertise; Audit Committee Independence; Audit Committee Meetings; Audit Committee size; Earnings per Share